Living among catholics or among ‘heretics’ mobility and religious control of Magdalena Hodston, a protestant woman in Cartagena de Indias, 1711-1713 (Tzintzun, Revista de Estudios Históricos, 2022)
Between 1711 and 1713 the Inquisition of Cartagena de Indias prosecutedMagdalena Hodston, a female of “English nation”, who settled down in that portcity, generating great questions. Her case is significant because there are no studieson the subject. In this sense, her case will allow us to reflect not only on her lifestory, but also on the religious control exercised by the Inquisition and the mobilityof Protestant women in the Hispanic dominions, which is framed in the diplomaticrelations of the Spanish Monarchy with other kingdoms.
Keywords: inquisition; women; protestants; Cartagena de Indias